2009
DOI: 10.1152/jn.91104.2008
|View full text |Cite
|
Sign up to set email alerts
|

Excitability at the Motoneuron Pool and Motor Cortex Is Specifically Modulated in Lengthening Compared to Isometric Contractions

Abstract: Neural control of muscle contraction seems to be unique during muscle lengthening. The present study aimed to determine the specific sites of modulatory control for lengthening compared with isometric contractions. We used stimulation of the motor cortex and corticospinal tract to observe changes at the spinal and cortical levels. Motor-evoked potentials (MEPs) and cervicomedullary MEPs (CMEPs) were evoked in biceps brachii and brachioradialis during maximal and submaximal lengthening and isometric contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
138
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(159 citation statements)
references
References 49 publications
14
138
7
Order By: Relevance
“…The reduction has been reported both when resisting an imposed force at a constant velocity (Duclay et al, 2011;Gruber et al, 2009) and when lowering an inertial load even with the background EMG activity matched, a method that controls partly for differences in the recruitment gain in the motor neurone pool (Pierrot-Deseilligny and Burke, 2012), during both types of anisometric contractions with the elbow flexor (Abbruzzese et al, 1994;Sekiguchi et al, 2001) and soleus (Sekiguchi et al, 2003) muscles. With this approach, MEP amplitude is reduced in the soleus during a maximal lengthening contraction of the plantar flexors compared with a maximal shortening contraction ( Fig.…”
Section: Displacement (I) Rectified Surface Emg (Ii) and Intramusculmentioning
confidence: 97%
See 3 more Smart Citations
“…The reduction has been reported both when resisting an imposed force at a constant velocity (Duclay et al, 2011;Gruber et al, 2009) and when lowering an inertial load even with the background EMG activity matched, a method that controls partly for differences in the recruitment gain in the motor neurone pool (Pierrot-Deseilligny and Burke, 2012), during both types of anisometric contractions with the elbow flexor (Abbruzzese et al, 1994;Sekiguchi et al, 2001) and soleus (Sekiguchi et al, 2003) muscles. With this approach, MEP amplitude is reduced in the soleus during a maximal lengthening contraction of the plantar flexors compared with a maximal shortening contraction ( Fig.…”
Section: Displacement (I) Rectified Surface Emg (Ii) and Intramusculmentioning
confidence: 97%
“…The tension-regulating inhibitory hypothesis An often-evoked suggestion for the lower voluntary activation during maximal lengthening contractions is the intervention of a tension-regulating mechanism intended to protect the muscletendon unit against excessive tension (Amiridis et al, 1996;Del Valle and Thomas, 2005;Gruber et al, 2009;Seger and Thorstensson, 2000;Westing et al, 1990Westing et al, , 1991. Despite earlier animal and human experiments having shown that the Golgi tendon organs (Ib inhibition; see Houk and Henneman, 1967;Priori et al, 1998) are not responsible for the 'clasp-knife' phenomenon triggered at high muscle forces (Rymer et al, 1979), the proponents of this protective strategy assume that the inhibitory action of the Golgi tendon organs is to depress the responsiveness of the motor neurones, thereby limiting the force produced by the muscle-tendon unit.…”
Section: Control Of Maximal and Submaximal Lengthening Contractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes observations that voluntary activation, electromyography (EMG), force generation and spinal motoneuron excitability are all different during lengthening contractions [1,2]. Furthermore, recent evidence from studies using a range of neurophysiological and neuroimaging techniques have provided compelling support for distinct patterns of cortical activity during lengthening contractions [3][4][5][6][7][8][9][10][11]. In addition, lengthening contractions are also associated with reduced motor performance [12][13][14].…”
Section: Introductionmentioning
confidence: 99%